LITERASI KEUANGAN SYARIAH PENGELOLA KOPERASI PONDOK PESANTREN AN-NAWAWI KEC. GEBANG, KAB PURWOREJO - Sri Lestari; Hajar Mukaromah (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2018)
This research discuses about literacy of sharia finance aimed to observe to what extent the knowledge of the cooperation manager of Islamic Boarding School towards the literacy of sharia finance determined by the demographical factor, the factor that has a relation with the literacy of finance included education, sex and income. However, this research would focus on the relationof demographical factor and literacy of finance sharia in the perspective of education that is at the level of education and the origin of education of an an dividual in mananging the finance. This research used the quantitative research method in which the measurement was implemented using Continuous Rating Scale (CLS) whith the measurement category of literacy of finance divided into three: high, medium, and low. The variabel in this research included: finance literacy (management of personal finance, saving, investment, assurance), education level (SMU/MA below and undergraduate program above), origin of education (general, religiosity). The research results showed that there was no any difference of sharia finance literacy as seen from the educational level and the origin of education of the cooperation manager of Islamic Boarding School An-Nawawi. This was not in line with the hypothses. However if analyzed in each indicator, then in the assurance, there was a significant influence resulting in the significance at < 0,05. Then, there was a significant influence either in educational level and origin of education